Conceptual Field of “SIN” in Context of Studying Linguistic Mentality - L. I. Zhukovskaya; V. V. Saygin (Научный диалог)
The article describes the principles of modeling the conceptual field of “SIN” in the context of studying national language according to the mentality of the Russian language. The purpose of the study is description of content and structural features of the language organization of conceptual field as a basic combat unit of language mentality. The research centers on language and text features of syntagmatic, paradigmatic and associative relations between the words sin , repentance and virtue - the representatives of the conceptual field of “SIN” identified through the analysis of the data extracted from dictionaries and also from the National corpus of the Russian language. Theoretical framework of the study is based on the principles of analysis of ways of conceptualizing the world as a source of formation of the phenomenon of “linguistic mentality.” The study uses the methodology of conceptual analysis developed at the Department of Teaching the Russian language in Other Language Environments, Lobachevsky State University of Nizhny Novgorod. The authors prove that the original basic structure of the conceptual field of “SIN” forms a multicomponent conceptual bunch of SIN - REPENTANCE IS -VIRTUE. In this case, the conceptual field of “SIN” is structured differently in relation to religious and non-religious, secular layer of this conceptual content. Practical significance of the research is that the main results can be used in University teaching of disciplines of the cultural linguistics cycle and in the practice of compiling dictionaries of concepts and of linguistic thesauri.